Financial inclusion and savings and loan cooperatives in Mexico - Lara Gómez, Graciela; Rubio Ugalde, Gema Jazmín; Hurtado Maldonado, Jesús (REVESCO. Revista de Estudios Cooperativos, 2025)
The aim of this article is to outline the legal framework and public policies that underpin the participation of savings and loan cooperatives in financial inclusion strategies in Mexico. The analysis is grounded in a theoretical approach that posits access to and use of financial services as key factors in mitigation inequality and poverty among vulnerable populations. Using the exegetical method, this study analyzes the legal mechanisms, institutional frameworks, and regulatory applications that structure the operation of savings and credit cooperatives, in the context of financial inclusion. It also examines public policies and evaluates the progress made in addressing financial exclusion. The findings of this research indicate that cooperatives, by virtue of their mission rooted in solidarity and mutual support, are particularly well-positioned to implement initiatives aimed at eliminating financial exclusion. The study reaffirms that financial education, a legal framework that ensures security and legal certainty, as well as the integration of technological infrastructure in remote areas, are essential components for achieving the broader objective of promoting financial inclusion across the population.